The Effect of Security Levels, Resource Requirements, and Scalability on User Acceptance of Cloud Computing Systems in Technology Companies in Indonesia - Muhamad Bakhar; Muchamad Sobri Sungkar (Westscience Press, 2023)
This research investigates the impact of security levels, resource requirements, and scalability on user acceptance of cloud computing systems in technology companies in Indonesia. Employing a quantitative approach, the study involves a sample of 250 respondents from diverse companies. The research employs Structural Equation Modeling with Partial Least Squares (SEM-PLS) for data analysis. Descriptive statistics, measurement model assessment, discriminant validity analysis, and structural model assessment are conducted to explore relationships between variables. Results reveal significant positive relationships between security levels, resource requirements, scalability, and user acceptance. The study provides insights into the critical factors influencing cloud computing adoption in Indonesia's dynamic technological landscape.